Study the Protection of Victim Rights to the Criminal Justice System of India: Addressing the Challenges of Victim Protection in the Indian Criminal Justice System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In India the condition of the victim are the worst because of there no separate legislation for their compensation and restitution and all restitution or rehabilitation services are available only to the accused in place of victims. In India, long way to go before we achieve victim justice. There are several obstacles in India in the process of preventing victimisation and protecting victims, which are being addressed through certain constructive methods. In India, there is no distinct law for crime victims. The central government has made no sustained effort to indorse a national law for victims. The State governments and union territories of India formed the Victim compensation Scheme in regard to the section 357-A of the code but these schemes are not so effective in comparison to the other countries of the world.